Unusual Presentation of Pyogenic Granuloma of Buccal Mucosa - S C Selvamuthukumar; Nalini Ashwath; V Anand (Wolters Kluwer Medknow Publications, 2010)
Exophytic growth of the oral cavity often presents a diagnostic challenge because a diverse group of pathologic processes can produce such lesions. Among the exophytic growth of oral cavity inflammatory hyperplasia stands the most common etiology. The pyogenic granuloma is the most common type of inflammatory hyperplasia found in the oral cavity especially in gingiva. Extragingival occurrence of pyogenic granuloma is usually rare. Hence, we report such a rare presentation of pyogenic granuloma on buccal mucosa in a 35-years-old male.